SPECIES OF THE FAMILY LEPTOPODIDAE (HETEROPTERA) IN SERBIA (Acta Entomologica Serbica, 2018)
Erianotus lanosus (Dufour, 1834) was collected for the first time in Serbia. Leptopus marmoratus (Goeze, 1778) is the other species from the Leptopodidae family that has been found in Serbia to date. In Europe, four species of the family Leptopodidae are distributed: Erianotus lanosus (Dufour), Leptopus hispanus Rambur and Leptopus marmoratus (Goeze) and Patapius spinosus (Rossi).